اهمية تطوير المنتجات البنكية في تحريك سلوك المستهلك دراسة حالة للمنتجات البنكية الاسلامية - بن سعد سمية; طيبي فاطمة الزهراء; بن قشوة جلول (جامعة عمار ثليجي الاغواط, 2022)
This study aims to know how to develop new banking products and their role in motivating consumer behavior. To this end, we have collected information that includes both the bank and consumers, as the importance of the study enables the impact of new banking products on the Algerian customer’s choice of these products, and in order to achieve the objectives of the study we have By distributing a sample of a questionnaire through which we concluded that there is a statistically significant effect on the characteristics of new banking products in moving consumer behavior